The effect of temperature and irradiation dose on the luminescence properties of EU 3+ doped phosphate glasses; Известия вузов. Физика; Т. 57, № 12/3 - Lisitsyn V. M. Viktor Mikhailovich (2014, 2014)
Заглавие с экрана